IMPLICATIONS OF TOLERANCE CHARACTER VALUES IN HOME-STAY ACTIVITIES: A MULTICULTURAL EDUCATION PERSPECTIVE IN ASSALAAM SENIOR HIGH SCHOOL - Nurdin, Immawan; Sutama, Sutama (Profetika: Jurnal Studi Islam, 2020)
Character education is very important to be implemented in school educational institutions, so that more attention is needed to minimize the emergence of various social diseases, such as damage to morals, morals and ethics. This study aims to determine the impact of home-stay activities on the emergence of tolerant character values in multicultural situations among students of SMA Assalaam Surakarta Indonesia. This researcher used a qualitative method with an ethnographic design. Researcher as an instrument by setting the focus of research to analyze the data obtained inductively. Collecting data through observation, semi-structured interviews with teachers and home stay participants, and documentation. The results showed that home-stay activities educate students to behave tolerantly in multicultural situations and contribute to forming a person who is aware of democratic values. To realize democratic education based on awareness of the values of tolerance built by multicultural social facts. In addition, it is contained in education based on out-door activities such as home-stay, which builds students' personalities with spiritual, intellectual, social, emotional and skills which are summarized in multicltural educational practices. Based on the results of this study, home-stay activities are very effective as a model of multicultural education with values of tolerance as the basis for the realization of democratic education. This home-stay-based multicultural education is an inspiration for environmentally friendly educational practices.